Navigating the Digital Transformation Landscape in Indonesia: A Qualitative Sectoral Analysis - Haryanti, Tining; Rakhmawati, Nur Aini; Subriadi, Apol Pribadi (Digest of technical papers - IEEE International Conference on Consumer Electronics, 2024)
This study explores the factors influencing digital transformation (DX) in Indonesia through a qualitative analysis of various sectors, focusing on C-level executives. It identifies seven key dimensions-Strategy, Organization and Structure, Technology, Transformation Process, Employee, Customer, and Culture-comprising thirty-two sub-dimensions that impact DX success. Validation and reliability were confirmed with a high global Alpha Biner (0.965) and semantic data alpha values (0.933 to 0.99). The cultural dimension posed the greatest challenges, with issues such as the willingness to change and social collaboration. The proposed solutions include community counseling and educational activities. The government sector faces significant DX hurdles owing to rigid structures, budget constraints, and skill gaps. This study highlights the need for sector-specific adjustments to accurately measure digital maturity and calls for further empirical research across sectors. These findings provide a framework for organizations to independently assess and enhance their DX progress.